Gamification of West Kalimantan local wisdom through a visual-interactive interface: Development of an inclusive edugame for deaf students - Irwan Adhi Prasetya; Novi Aryani Fitri; Muhammad Faqih Dzulqarnain; Muhamad Syafarudin Ilham (Jurnal Pendidikan Informatika dan Sains, 2026)
This study aims to develop an inclusive cooking-themed edugame based on West Kalimantan culture for deaf students through the integration of a visual-interactive interface, a BISINDO avatar, and local cultural content. The development employed the ADDIE model, comprising needs analysis, interface design, and Unity-based prototype creation involving 3D modeling, rigging, and initial integration of BISINDO animation. The edugame was designed to be interactive, multimodal, and readily accessible in accordance with the characteristics of users with special needs. The implementation and validation results indicate that the edugame falls within the highly feasible category, with an acceptance rate of 80.94%. Overall, the edugame received positive user responses regarding readability, interactivity, clarity of instructions, and the appropriateness of its cultural content. This study demonstrates that the integration of gamification, BISINDO, and local wisdom has the potential to serve as an inclusive and adaptive learning strategy for deaf students